Pandangan Alkitabiah Terhadapa Penderitaan Dalam Konteks Indonesia - Filiani Filiani; Aprianus Lendrik Moimau (Publisher STPKat, 2023)
In the beginning God created humans and hoped that humans could reflect life as God's glorious creation, that is, in the image and similarity of God. For Irenius, the image of God meant “Human nature as a rational and free being. In connection with the term